Tax avoidance and optimal income tax enforcement - Duccio Gamannossi degl'Innocenti; Matthew D. Rablen (Institute for Fiscal Studies (IFS), 2017)
We examine the optimal auditing problem of a tax authority when taxpayers can choose both to evade and avoid. For a convex penalty function the incentive-compatibility constraints may bind for the richest taxpayer and at a positive level of both evasion and avoidance. The audit function is non-increasing in reported income, and is higher for progressive tax functions than for regressive tax functions. Higher marginal tax rates increase the incentives for non-compliance, overturning the well-known Yitzhaki paradox.
Keywords: H26; K42; D82; H21; 330; Tax avoidance; Tax evasion; Optimal auditing; Tax administration